Identical - Turow, Scott; Leyva, Henry; Smith, Cheryl; Rapkin, David; Hachette Audio (Firm) (New York : Hachette Audio, 2013)
Based loosely on the myth of Castor and Pollux, this is the story of identical twins Paul and Cass Giannis and the complex relationships between their family and their former neighbors, the Kronons. The novel focuses principally on events in 2008, when Paul is a candidate for Mayor of Kindle County, and Cass is released from the penitentiary, 25 years after pleading guilty to the murder of his girlfriend, Athena Kronon. The plot centers on the re-investigation of Athena's murder, carried out together by Evon Miller, an ex-FBI agent who is the head of security for the Kronon family business ZP, and private investigator Tim Brodie, 81, a former homicide detective.
Keywords: Twins -- Fiction; Brothers -- Fiction; Political candidates -- Fiction; Murder -- Fiction -- Investigation; Audiobooks; Suspense fiction; Audiobooks